F.R. David : Very Good - Holder, Will; Abbott, Paul; Anastas, Rhea; Anderson, Henry; Butt, Aisha; Byatt, Lucy; Eckhardt, Judith & Julia; Farrer, Cicely; Greene, Keira; Gruijthuijzen, Krist; Mackey, Nathaniel; Meginsky, Jake; et al. ([s.l.] : uh books with Kw Institute for Contemporary Art, 2020)
Gruijthuijsen, Krist ; Sarif, Alma ; Anastas, Rhea ; Anderson, Henry ; Butt, Aisha ; Byatt, Lucy ; Eckhardt, Judith ; Eckhardt, Julia ; Farrer, Cicely ; Greene, Keira ; Mackey, Nathaniel ; Meginsky, Jake ; Reinartz, Philip ; Reynolds, Alex ; Sperlinger, Mike ; The Creaking Breeze ; Thomas, Abby
boek